Penerapan QRIS dalam Mendukung Transaksi Digital pada UMKM Ayam Goreng Alfi Barkah - Caroline Sari Simbolon; Grace Orlyn Sitompul; Shela Layti Siagian; Yosafath Anggit Laksana (CV. ITTC INDONESIA, 2026)
This study aims to assist Alfi Barkah Fried Chicken MSMEs in implementing a digital payment system through the Indonesian Standard Quick Response Code (QRIS) to improve transaction efficiency and business financial management. Prior to the use of QRIS, the only payment methods available were cash and bank transfers, which still required manual payment verification and were not connected to an automatic transaction recording system. This situation made the transaction process impractical and made it difficult for business owners to accurately monitor cash receipts. The methods used in this activity included interviews, training, and assistance in the process of creating and using QRIS in business operations. The evaluation was carried out by comparing the conditions before and after the implementation of the digital payment system. The results of the activity show that the use of QRIS can speed up the payment process, facilitate transaction monitoring, and make financial records more structured. In addition, after the implementation of QRIS, there was an increase in daily income of around 20%. This shows that QRIS plays an important role in supporting the digitization of transactions and the development of MSME businesses.